Chemotherapeutic drug delivery nanoplatform development: From physicochemical to preclinical evaluation - Kontogiannis, Orestis; Selianitis, Dimitrios; Palikaras, Konstantinos; Pippa, Natassa; Pispas, Stergios; Efstathopoulos, Efstathios; Gazouli, Maria (Int. J. Mol. Sci., 2024)
Through this study, the synergistic behavior of small-molecular-weight, amphiphilic surfactant molecules and the triblock copolymer Pluronic 188 was extensively evaluated based on their ability to formulate nanocarriers with novel properties for the delivery of class II and IV (biopharmaceutical classification system) chemotherapeutic compounds. The combination of four different surfactants at multiple weight ratios and twelve initially formulated nanosystems resulted in four hybrid delivery platforms, which were further studied in terms of multiple physicochemical characteristics, as well as their stability in protein-rich media (fetal bovine serum/phosphate-buffer saline). Finally, we obtained a single final nanoformulation that exhibited a high loading capacity (%EE ≥ 75%) and a sustained drug release profile under physiological conditions (model drug methotrexate), without altering the original physicochemical characteristics of the carrier. With a mean hydrodynamic radius (Rh) of less than 70 nm, a polydispersity index of 0.219, and no protein complexation, the system is a suitable candidate for in vivo, intravenous, and/or intramuscular administration. The cytotoxicity and genotoxicity of both loaded and unloaded carriers were evaluated through the examination of the upregulation or downregulation of apoptosis-related pathways. Multiple conventional 2D and 3D spheroidal conformations were used for these assessments, including HEK293, HCT-116, and MCF-7 cell lines, the results of which stressed the safety and biocompatibility of the empty nanocarrier. Additionally, experiments on Caenorhabditis elegans were conducted to evaluate the system's in vivo toxicity, focusing on developmental stages, egg-laying behavior, and locomotion. Nanosystems studied in terms of chemotherapeutic encapsulation have mostly focused on the physiochemical aspect of the development of such novel delivery platforms, with only few exceptions proceeding step-by-step from cellular 2D to 3D to in vivo experimentation. The present study offers a holistic view of the behavior of such a novel system, advancing our understanding of the capabilities of polymeric/surfactant-based nanodelivery platforms.
Keywords: 3D cell culture; C. elegans; MTS assay; Pluronic 188; real-time PCR; thin-film hydration